Renal Vein Thrombosis as an Initial Presentation for Systemic Lupus Erythematosus in a 32-Year-Old Sudanese Male: A Case Report in Palestine - Ayah Abu Lehia MD; Adham Itbaisha MD; Lila H. Abu-Hilal MD; Abdullah Hamamdah MD; Adeeb Darras MD; Abdullatif Shawar MD (SAGE Publishing, 2024)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease known for its diverse clinical presentations, and one severe complication is lupus nephritis (LN), which significantly contributes to morbidity and mortality. While LN often presents within the first 5 years of SLE diagnosis, renal vein thrombosis (RVT) is a rare vascular complication with a high risk of mortality and morbidity. This case report discusses the rare occurrence of RVT as the initial presentation of SLE in a 32-year-old Sudanese male patient, currently working in Palestine, presenting with flank pain, hematuria, fever, and lower limb edema. The case details the patient's symptoms, examination findings, and extensive laboratory and imaging workup leading to the diagnosis. This report highlights the rare association between RVT and SLE, emphasizing the importance of maintaining a high index of suspicion for SLE in patients with multisystem involvement, especially in males, where the diagnosis may be overlooked due to its lower prevalence. Early recognition can improve patient outcomes and reduce the risk of complications. Further research is needed to better understand the connection between RVT and SLE and to develop more effective treatment strategies.